EFFECT OF ORGANIZATIONAL CULTURE, ORGANIZATIONAL COMMITMENT, AND LOYALTY ON EMPLOYEE PERFORMANCE OF PT. NISSAN MOTOR INDONESIA SURABAYA - Tri Setyo Herdianto, Tri Andjarwati; Setyo Herdiyanto (RJABM (Research Journal of Accounting and Business Management), 2022)
The aim of this study is to examine and analyze the influence of corporate culture, corporate engagement and loyalty on employee performance at PT. Nissan Motor Indonesia Surabaya. The hypothesis of this study is that company culture, engagement and loyalty of employees have an impact on employee performance. The data was collected by distributing questionnaires to 25 participants. SPSS version 25 was used for data analysis in this study. The sampling technique used was saturated sampling. The data analysis technique used is validity test, reliability test, classic acceptance test, multiple linear regression analysis, multiple correlation analysis and determination analysis. The F-test and the t-test are used as hypothesis tests.Based on the research of multiple linear regression analysis, Y = 16,613 + 0.428 X1 + 0.464 X2 + 0.595 X3 + e. The results of the F-hypothesis test show that organizational culture, organizational commitment and loyalty simultaneously have a significant influence on employee performance; this can be seen from the Sig value of 0.000 <0.05 and the value of F_count 18.899> F_table 3.07. The results of the t-hypothesis test indicate that the variable organizational culture sometimes has a significant influence on employee performance, this can be seen from the sig value of 0.000 <0.05 and the t_count value of 3,311> t_table 2,080. Partial commitment of the organization has a significant influence on employee performance, this can be seen from the sig value of 0.032 <0.05 and the value of t_count 2.303> t_table 2.080. Loyalty sometimes has a significant influence on employee performance, this can be seen from the sig value of 0.001 <0.05 and the t_count value of 3.974> t_table 2.080. The results of the t-hypothesis test show that the variables organizational culture, organizational commitment and loyalty partially influence employee performance.Keywords: Employee Performance, Loyalty, Organizational Commitment, Organizational Culture.